Actualization of Religious Moderation in Multicultural Society in Kerta Buana Village, Kutai Kartanegara Regency - Alifia Nur Rizkilah Slamet; Noor Hasanah (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2024)
This study explores the actualization of religious moderation within the multicultural community of Kutai Kartanegara. Efforts to promote principles of religious moderation remain a focus, particularly among the multicultural population of Kerta Buana Village in Tenggarong Seberang District, Kutai Kartanegara Regency, East Kalimantan Province. This study identifies strategies for implementing religious moderation in multicultural communities, offering an adaptable model for other regions across Indonesia. This research utilizes a case study approach, with data sourced from interviews and field findings. The study aims to develop a conceptual framework for villages seeking to actualize religious moderation, specifically within multicultural settings. A multicultural society is one characterized by diversity across ethnicities, cultures, languages, and religions. Such diversity requires proactive measures in village governance and community engagement to foster harmony, peace, and tolerance, while preventing the formation of divisive, intolerant groups within or among multicultural communities.